AKAP9 supports spermatogenesis through its effects on microtubule and actin cytoskeletons in the rat testis. Issue 10 (27th September 2021) - Wu, Siwen; Li, Linxi; Wu, Xiaolong; Wong, Chris K. C.; Sun, Fei; Cheng, C. Yan
Abstract: In mammalian testes, extensive remodeling of the microtubule (MT) and actin cytoskeletons takes place in Sertoli cells across the seminiferous epithelium to support spermatogenesis. However, the mechanism(s) involving regulatory and signaling proteins remains poorly understood. Herein, A‐kinase anchoring protein 9 (AKAP9, a member of the AKAP multivalent scaffold protein family) was shown to be one of these crucial regulatory proteins in the rat testis. Earlier studies have shown that AKAP9 serves as a signaling platform by recruiting multiple signaling and regulatory proteins to create a large protein complex that binds to the Golgi and centrosome to facilitate the assembly of the MT‐nucleating γ‐tubulin ring complex to initiate MT polymerization. We further expanded our earlier studies based on a Sertoli cell‐specific AKAP9 knockout mouse model to probe the function of AKAP9 by using the techniques of immunofluorescence analysis, RNA interference (RNAi), and biochemical assays on an in vitro primary Sertoli cell culture model, and an adjudin‐based animal model. AKAP9 robustly expressed across the seminiferous epithelium in adult rat testes, colocalizing with MT‐based tracks, and laid perpendicular across the seminiferous epithelium, and prominently expressed at the Sertoli‐spermatid cell–cell anchoring junction (called apical ectoplasmic specialization [ES]) and at the Sertoli cell–cell interface (called basal ES, which together with tight junction [TJ] created the blood–testis barrier [BTB]) stage specifically. AKAP9 knockdown in Sertoli cells by RNAi was found to perturb the TJ–permeability barrier through disruptive changes in the distribution of BTB‐associated proteins at the Sertoli cell cortical zone, mediated by a considerable loss of ability to induce both MT polymerization and actin filament bundling. A considerable decline in AKAP9 expression and a disruptive distribution of AKAP9 across the seminiferous tubules was also noted during adjudin‐induced germ cell (GC) exfoliation in this animal model, illustrating AKAP9 is essential to maintain the homeostasis of cytoskeletons to maintain Sertoli and GC adhesion in the testis.